2016
DOI: 10.1111/sjop.12328
|View full text |Cite
|
Sign up to set email alerts
|

A two wave cross‐lagged study of work‐role conflict, work‐family conflict and emotional exhaustion

Abstract: By using a two-wave panel design, the present study aimed to study causal, reversed, and reciprocal relations among work-role conflict, work-family conflict, and emotional exhaustion. The Conservation of Resources theory was applied as a theoretical framework. The study was conducted in a large Norwegian oil and gas company (n = 1703). The results demonstrated positive cross-lagged effects of work-role conflict and work-family conflict on emotional exhaustion. In addition, emotional exhaustion predicted work-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 59 publications
1
18
0
1
Order By: Relevance
“…Because the data used are cross-sectional, no causal conclusions can be drawn on the association between WFC and SRH. Thus, it cannot be ruled out that selection effects may play a role in the association between WFC and health and that poorer health leads to higher WFC, as has already been shown elsewhere (Jensen, 2016; Leineweber et al, 2013; Neto et al, 2016).…”
Section: Discussionmentioning
confidence: 88%
“…Because the data used are cross-sectional, no causal conclusions can be drawn on the association between WFC and SRH. Thus, it cannot be ruled out that selection effects may play a role in the association between WFC and health and that poorer health leads to higher WFC, as has already been shown elsewhere (Jensen, 2016; Leineweber et al, 2013; Neto et al, 2016).…”
Section: Discussionmentioning
confidence: 88%
“…In this regard, for workers with low family support, job resources, especially POS, are particularly salient and their job satisfaction and psychological well-being might be directly dependent on this work resource and less sensitive to their job strain (Tetrick et al, 2000). These results seem to indicate that the transfers of resources between different domains do not follow a pattern of reciprocity, contrary to what usually occurs between work-family conflict and outcomes (Demerouti, Bakker & Bulters, 2004;Jensen, 2016).…”
Section: Implications For Theory and Researchmentioning
confidence: 92%
“…It is defined as a specific alteration in mood (e.g., sadness, loneliness, and apathy) and a negative self‐concept that leads to self‐reproach (Beck & Alford, ). Recent literature has indicated that stress is related to depression across different age groups (adolescents: Moksnes, Bradley Eilertsen & Lazarewicz, ; adults: Jensen, ; adolescents to elderly: McNicol & Thorsteinsson, ), yet, there is a lack of relevant studies focusing on college students. For example, Dyson and Renk () examined the relationships between depressive symptomatology and levels of stress in 74 college freshmen.…”
Section: Introductionmentioning
confidence: 99%